HOME REHABILITATION PROGRAM FOR FARMERS SUFFERING LOW BACK PAIN: A CASE STUDY - Hartatik, H; Rahman, Farid; Riza, Oni Iftar (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: Low back pain is one of the major problems faced by a worker. According to data from a survey by work-related diseases of 43,000 workers in agriculture, 27,000 of them complain of low back pain. Wrong posture done by workers for a long time will trigger the emergence of pain in the lower back. Case Presentation: The method used in this study is a case report from a patient low back pain at Ngawi Hospital with a identity TN.BC with the age of 56 years. The patient felt pain in the lower back in November 2020 because he often lifted heavy loads while doing activities in the fields such as lifting fertilizers, lifting spray tanks. Management and Outcome: the provision of infrared, TENS and Core stability exercise (CSE) is one of the effective methods to reduce complaints of pain in the lower back Discussion: This IR application given to LBP patients will provide a relaxing effect and help blood flow to the area. Giving TENS here is used to block the pain that appears. This type of Core Stability exercise aims to improve neuro-omuscular control , endurance, central muscle strength to maintain dynamic spinal stability. CSE can control during the movement of weight transfer, functional activities such as sitting, standing and walking. We all need a good Core stability program to prevent low back pain from initiating limb movement, for proper utilization of muscle strength and to improve performance. Conclusion: Handling physiotherapy in the form of giving IR, TENS and CSE can reduce complaints of low back pain that farmers complain about.